Induced rolling moment for NACA4412 plain and flapped wing - Elsayed, Omer Ali; Kwon, Kijung; Asrar, Waqar; Omar, Ashraf Ali E. (Emerald Group Publications Limited, 2010)
Purpose – The paper aims to compute rolling moments on a follower aircraft wing due to vortices generated by a plain and flapped NACA4412 wing using experimental particle image velocimetery (PIV) data.